MANAGEMENT BELIEFS AND PRACTICES OF ELEMENTARY SCHOOL HEADS ON INSTRUCTIONAL LEADERSHIP - Buban, Louie M.; Digo, Gerry S. (International Journal of Research -GRANTHAALAYAH, 2021)
This study carry out a content analysis on the features of School Heads Development Program (SHDP) project outputs of school heads in the DepEd Schools Division of Sorsogon Province, Philippines. As part of the content analysis, the SHDP project outputs were categorized for instructional leadership. Also, the management beliefs and practices of school heads on instructional leadership along two-dimensional contracts were out in this study. The statistical tool used were Spearman and computed through the SPSS software program. The results were presented by frequencies in a descriptive way. The date collection technique was survey questionnaire and interview. The results indicated that the features were done, generative, systematic, standard-based and shared manner. School heads’ beliefs are strongly they frequently practiced instructional leadership. It can be concluded also that the management beliefs and practices of school heads on instructional leadership have significant relationship on communicating the school goals to conflict management as leadership process likewise, maintain high visibility to change process, meaning that school heads make use of leadership processes to perform well the instructional leadership function of an instructional leader.